Different G proteins mediate the opioid inhibition or enhancement of evoked [5-methionine]enkephalin release. - Gintzler, A R (1991)
This laboratory has previously demonstrated that there is an opiate receptor-mediated, concentration-dependent modulation of the electrically stimulated release of enkephalin from the guinea pig myenteric plexus. Low doses of opioids (nanomolar) enhance release, whereas higher concentrations (10-100 nM) inhibit release. We now demonstrate that the in vivo i.p. administration of the islet-activating protein from pertussis toxin (PTX; 50 micrograms/500 g of body weight) markedly diminishes the potency of mu, delta, or kappa-selective opioids to inhibit the evoked release of enkephalin. In contrast, PTX is without effect on the enhancement of enkephalin release observed after treatment with nanomolar concentrations of the above opioids. Conversely, pretreatment with cholera toxin (CTX; 0.01 nM for 3 hr in vitro) has no effect on the mu, delta, or kappa opioid inhibition of evoked enkephalin release but abolishes the ability of nanomolar concentrations of these agonists to enhance stimulated enkephalin release. These data indicate that different classes of guanine nucleotide-binding proteins (G proteins) appear to mediate the opioid enhancement or inhibition of stimulated enkephalin release. Furthermore, they suggest that a PTX-sensitive G protein (Gi or Go) and a CTX-sensitive G protein (Gs) are integral components of the mechanism that mediates opioid inhibition and opioid enhancement, respectively, of evoked enkephalin release. To our knowledge, this report represents the first demonstration that Gs-coupled opiate receptors (in addition to those that are coupled to Gi) can modulate transmitter release.